The master plan of school equipment in the construction of the city (2005)
The Master Plan school equipment is part of the ordering and regularization process that undergoes all around the country. It has the task to delineate the ordering principles for endowment services, to adopt urban standards and provide indicators to allow future building and implantation planning. This Master Plan is a privileged scenery for future management and ordering processes because it allows to confront and include space in the educational system, reinforces the centralities structure of the territorial plan of the POT (Territory Ordering Plan) for Bogotá, and proposes a new stage in the city territorial planning through the urban project as a definitive topic for the program, creating in this way a profound relation between the educative dimension of the city and the urban dimension of the education.